Sufu- and Spop-mediated downregulation of Hedgehog signaling promotes beta cell differentiation through organ-specific niche signals - Theodora Yung (Nature Portfolio, 2019)
Dynamic mesenchyme derived signals are known to direct proper organ formation and cell specification in vivo. Here the authors show in mice that mesenchyme derived Hedgehog and Wnt instruct the formation of the pancreas and beta cells, and that Wnt inhibition promotes beta cell formation from human pluripotent cells.